Considerations on the use of Diagnostic Tools in the Prevention of Prostate Cancer - Juan Santiago Serna Trejos; Stefanya Geraldine Bermúdez Moyano (Revista Finlay)
The therapeutic approach in the prevention of prostate cancer is a clinical challenge for the health professional who is preparing to face this condition. This happens because, among other reasons, there are some social references with their respective connotations in relation to the perception of the physical screening examination for prostate cancer.